Pengaruh Model Project Based Learning Berbantuan Four Square terhadap Kemampuan Menulis Teks Argumentasi Siswa Kelas XI SMA Negeri 12 Semarang dan Implikasinya dalam Pembelajaran Menulis - Naazil Maharani An Nuur; Herman Budiyono (Bhinneka: Jurnal Bintang Pendidikan dan Bahasa, 2026)
This study was conducted with the aim of explaining the influence of the project based learning model assisted by four square on the ability to write argumentative texts of class XI students of SMA Negeri 12 Semarang and its implications in learning to write. The method used in this study is a quantitative quasi-experimental approach with the nonequivalent posttest-only control group design. This design was chosen to determine the difference in the ability to write argumentative texts between students taught using the project based learning model assisted by four square and students taught with ordinary or conventional learning models. The results of the study showed that there was an influence of the project based learning model assisted by four square on students' argumentative text writing skills through the non-parametric Mann-Whitney U test of 115.500, a Z value of -4.973, and a significance value (Asymp. Sig. 2-tailed) of <0.001. Because the significance is smaller than 0.05, the null hypothesis (H₀) is rejected. It can be said that there was a significant difference between the results of the argumentative text writing test of students in the experimental class and the control class. Based on this, the application of the project based learning model assisted by four square can be used as an alternative learning model that has a positive influence on the ability to write argumentative texts of class XI students and has implications for writing learning.